Effects of Transport at Weaning on the Behavior, Physiology and Performance of Pigs - Sutherland, Mhairi A. (Animals (Basel), 2014)
SIMPLE SUMMARY: Pigs are commonly transported to separate production facilities at weaning to reduce disease transfer, enhance productivity and to improve overall operational efficiency. A review of the scientific literature suggests that these animals experience stress due to concurrent weaning and transport; however, gaps in the knowledge include the short and long term health and welfare implications of transporting pigs at weaning. Pig welfare and the efficiency of the swine industry may improve if science-based recommendations were in place. ABSTRACT: Transport of pigs to separate production facilities at the time of weaning is a common practice, primarily performed to reduce vertical transfer of disease and enhance production and overall farm efficiency. During transport, pigs are exposed to numerous stressors in conjunction with the stress experienced as a result of weaning. In this review, the behavioral and physiological response of pigs experiencing weaning and transport simultaneously will be described, including the effects of space allowance, season and transport duration. Based on the scientific literature, the gaps in the knowledge regarding potential welfare issues are discussed. Changes in behavior and physiology suggest that weaned pigs may experience stress due to transport. Space allowance, season and duration are aspects of transport that can have a marked impact on these responses. To date, the literature regarding the effects of transport on weaned pigs has primarily focused on the short term stress response and little is known about the effects of concurrent weaning and transport on other aspects of pig welfare including morbidity and mortality rates. Greater understanding of the short and long term consequences of transport on weaned pig welfare particularly in relation to factors such as trip duration, provision of feed and water, and best handling practices would benefit the swine industry. Furthermore, the development of guidelines and recommendations to enhance the short and long term welfare of weaned pigs in relation to transport are needed.